Palestine Under Attack: Humanitarian Principles in Case of Armed Conflict - Mochamad Kevin Romadhona; Sri Endah Kinasih; Rachmat Dimas Oktafenanda; Seokkyu Kim (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2025)
This research examines the application of International Humanitarian Law in armed conflicts and the involvement of countries in blockades to promote peace. It reveals that Humanitarian Law is enforced through the 1977 Additional Protocol, which governs international and non-international armed conflicts. The study also highlights Israel’s use of retaliatory Cast Lead operations in response to Hamas rocket attacks, which pose a threat to Israeli citizens’ safety. A narrative review is a research method that defines a topic, searches for relevant literature, organizes it, analyzes findings, and presents results in narrative form. It is suitable for broad overviews and provides flexible analysis. The ancient state of Israel, established by Shaul around 1025 BC, faced conflicts with the Palestinian nation, leading to the rise of groups like Fatah, Hamas, and the Palestine Liberation Organization. The Israeli Navy declared a blockade of the Gaza Strip in 2009, but the status of occupation remains questionable. International Humanitarian Law (IHL) is needed to protect victims affected by the conflict, and law enforcement mechanisms include diplomatic settlements, criminal investigations, and warnings. International Humanitarian Law is consistently respected and enforced, despite ongoing breaches, particularly in armed conflicts. Blockades, such as Israel’s infringement on Gaza, have resulted in widespread pain and loss of lives, highlighting the need for a more balanced approach to conflict resolution.